INFLATIONARY ELEVATED ENERGY PRICES AS THE MAIN FACTOR OF FUELLING ECONOMICALLY VIABLE ELECTRICITY PRODUCTION IN EU FOSSIL FUELS BASED THERMAL POWER PLANTS - Martin Bricl (Journal of Energy Technology, 2025)
The inflation in the last two years has driven the prices of the materials, goods as well as energy significantly higher. With steep increased inflation from month to month in the last two years, the overall inflation peaked at 9.2%, and core inflation at 6.2% in 2022 for the Eurozone area. This elevated prices are troubling the markets, industry and households, making the everyday business much more difficult for them than it was in pre-inflationary times. Also, additional geopolitical changes happened in the last two years (the war in Ukraine) which impacted the energy supply from the east significantly , primarily lowering the inflow of Russian gas to the European states to almost zero and banning the Russian crude from the international markets. This demanding condition on the energy market, as well as the very narrow time frame for building up a sufficient supply of energy for the winter of 2022 resulted in rather unexpectedly favourable conditions for energy generation (electricity or heat) from still operating coal based thermal power plants, which, in some way, is unacceptable, since we are exiting the coal based thermal power plants in EU actively, and trying to substitute them with renewables & alternatives. However, the aforementioned international markets stress test revealed that abandoning the fossil fuels from our everyday life will not be that easy, as we thought a decade ago.